Discourse, agency, and social license to operate in New Zealand - Newton M; Farrelly T; Sinner J (The Resilience Alliance)
The construction of discourse through choice of wording and sentence structure can affect power relations between people and groups. Social license to operate (SLO), broadly defined as the public’s acceptance or approval of a company and its operations, is an emergent concept in New Zealand’s marine economy. The way the public discourse around SLO is constructed and communicated can empower some at the expense of others, whether deliberately or inadvertently. This study employed critical discourse analysis to investigate how SLO is used in public documents relating to commercial activities in New Zealand’s marine environment between 1996 and 2017. Specifically, the study explores the implied power relations between government, industry, New Zealand’s Indigenous tribes (hereafter, iwi), communities, and other stakeholders. We find that industry and central government dominate SLO-related public discourse, and they frequently vest SLO agency with industry rather than community groups, iwi, or the wider public. Indeed, iwi are largely absent from the SLO discourse in public documents. Definitions of SLO vary extensively across the documents and are largely captured by industry and central government. We conclude that New Zealand’s marine SLO public discourse empowers industry at the expense of communities and the public, contrary to the notional intent of the concept.
Keywords: aquaculture; blue economy; corporate social responsibility; deep sea mining; fisheries; oil and gas; power; public documents